Sentence Patterns, Factual Content, and News Values in News Headlines: Their Impact on Readers’ Decisions to Engage with the Full Story - Yusuf, Tan Sri Zulfikar; Gunawan, Cecep; Jannah, Fani Nur (Indonesian Journal Publisher, 2025)
This study examines the relationship between sentence patterns, factual content, and news values in headlines with readers’ choices to read the full news content. Specifically, it tests the extent to which sentence patterns, factual content, and news values in headlines relate to readers’ decisions to engage with the articles. If there is a relationship between any of these three variables — whether individually or collectively — then headlines can be confirmed as predictors of readers’ choices to read the full news content. The results of this research will serve as a foundation for publishing study programs to develop more reliable and accurate guidelines for news writing. Media editorial teams will also be able to find more measurable and practical solutions, particularly regarding headline writing. This research employed a quasi-experimental method involving students from the Department of Graphic Engineering and Publishing. Treatments were designed using two types of news headlines as experimental treatments. The impact of these headline treatments on readers was analyzed using the Chi-Square statistical method. The results showed that, significantly, headlines written in active or passive sentence patterns containing opinions were more likely to be read by respondents than headlines containing factual statements. This trend was evident both in crime news and other general news categories, especially economic and health news. Therefore, it can be concluded that news value does not play a role in motivating people to read or ignore a news story.